Proyek Desain Pengolahan Air Limbah Domestik Skala Kawasan pada Kecamatan Pameungpeuk Kabupaten Bandung - Tsania Putri Fadhila; Nur Fadillah Ahmad; Faghira Muhammad Ghazani; Wildan Fadlullah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
A centralized wastewater treatment plant (IPAL) has been built in Pameungpeuk Sub-district of Bandung Regency in accordance with Bandung Regency Regional Regulation No. 27/2016. However, it was noted that by 2022 the coverage of wastewater services in Pameungpeuk sub-district had only reached 60%, while 40% were still discharging wastewater carelessly. Data from the Bandung Regency Health Office in 2020 showed that proper sanitation facilities in Pameungpeuk Sub-district reached 80.5%. This research aims to plan an area-scale domestic wastewater treatment design in Pameungpeuk Sub-district, Bandung Regency so that the domestic wastewater produced can be treated first in order to reduce the concentration of pollutants before flowing into the receiving water body. The method used is the Quantitative SWOT analysis method that refers to the Guidelines for the Preparation of Wastewater Management System Plans. Theresults of the analysis showed that integrated SPALD (SPALD-T) should be implemented in an integrated manner in the sub-district by considering the parameters of existing conditions, potential pollution and hazards, socio-economic characteristics of the community, public health conditions, education levels, and the availability of regulations regarding SPALD.